Book Review – The Economic History of India 1857–1947 - Singh, Dharmveer (AMC Indian Journal of Entrepreneurship, 2023)
The Economic History of India 1857–1947 by Tirthankar Roy is a comprehensive analysis of India’s economic evolution from 1857 to 1947. This book examined important facets of India’s economic history, including agriculture, industry, trade, finance, labor, and social and political dynamics. A prominent economist historian wrote it. In order to provide insights into the difficulties and changes that molded India’s economy as it moved from British colonial rule to independence, Roy used a multidisciplinary approach, drawing from various sources. Even though the book might use a more thorough examination of market analysis, it is nevertheless an important tool for academics, students, decision-makers, and ordinary readers interested in India’s economic history.